International maritime contracting and autonomy of will: validity and translational effectiveness of clauses conferring jurisdiction. Maritime Navigation Law (LNM) versus Brussels I bis. Judgment of the 6th Court of Justice, April 25, 2024, Maersk A/S y Mapfre España Compañía de Seguros y Reaseguros SA contra Allianz Seguros y Reaseguros SA y MACS Maritime Carrier Shipping GmbH & Co, C-345/22 - Álvarez Rubio, Juan José (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The judgment handed down by the Court of Justice on April 25 delimits and resolves with success, precision and jurisprudential coherence the interaction between the different rules that make up the regulatory framework (conventional, internal-state and European) regulating two key relative issues. to contracts for the maritime transportation of goods signed under a bill of lading: the determination of the law applicable to the validity requirements of the clauses conferring jurisdiction and the effectiveness against the third party holder of the bill of lading of such a clause conferring jurisdiction inserted in the same. The conclusion drawn by the Court of Justice in this judgment the scope and extension of the provisions contained in the Spanish LNM, which are displaced in its application to the benefit of Regulation 1215/2012.
Keywords: Marine transport; bill of lading; uses of the sector; opposability clause attributing jurisdiction; validity requirements; applicable law